Effectiveness of Woolwich Massage to Meet Adequacy of Breast Milk in Newborns - Septi Nurvitasari; Revi Pujiastuti; Arfiana Arfiana (Midwifery and Nursing Research, 2019)
Background: The recommendations of the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) in an effort to decrease the morbidity and mortality of infants and children, the child should be fed only breast milk (ASI) for at least 6 months. The highest failure of breastfeeding occurs in the first days after birth due to the low production of milk, so the need to increase milk production in the first days after birth.Purpose: The purpose of this study is to determine the effectiveness of Woolwich Massage to meet the adequancy of breast milk in newborn.Methods: This is a prospective study with quasi experiment research design. The population were primipara postpartum from day 8 to day 14. Technique of sampling using random technique that is side cluster. All samples were divided into two groups is 18 respondents as intervention group and 18 respondents as control group.Results: The results of this study indicate the effect of woolwich massage on meet the adequancy of breast milk in the newborn and significant difference in infant weight changes in the intervention group and control group (p value = 0.000 0.05). The adequency of breast milk can be assessed by monitoring the baby’s weight.Conclusion: It  is expected midwifes can teach woolwich massage techniques to ensure adequancy breast milk in the newborn. This effort can be a government policy to increase the coverage of exclusive breastfeeding in a region.